Sensitization and remediation effects on environmentally assisted cracking of Al-Mg naval alloys. (1st July 2018) - Seifi, M.; Ghamarian, I.; Samimi, P.; Collins, P.C.; Holroyd, N.J.H.; Lewandowski, J.J.
Abstract: Aluminum-magnesium alloys are ideal for a number of structural applications; however, alloys with magnesium content more than 3 wt% can become sensitized and susceptible to environmentally-assisted failure after exposure to moderately elevated temperatures for sufficient periods of time. Commercial Al-Mg alloys were tested in the as-received and sensitized conditions to investigate susceptibility to environmentally-enhanced cracking in fatigue crack growth. Slow strain rate testing (SSRT) of short-transverse (S-T) smooth tensile samples and fatigue crack growth testing of SEN bend specimens was also conducted in various loading orientations (L-T, L-S, S-L and S-T). Sensitization treatments included exposure to temperatures ranging from 60 °C – 175 °C for times ranging from 10 h to 20, 000 h. Under specific loading conditions and the presence of a local hydrogen source, IGSCC manifested itself as ST and SL plane splits during the cyclic loading of sufficiently sensitized L-S and L-T test specimens. The regimes of grain boundary cracking have been determined. Initial findings using ESBD data is suggestive that the high angle grain boundaries most likely to suffer IGSCC are those with a sharp gradient in the Taylor factor. Remediation treatments were also conducted on sensitized Al-Mg alloys in an attempt to reverse sensitization and restore alloy properties. While thermal remediation was somewhat effective in reducing the environmentally-sensitive fracture, this condition occurred at the expense of a loss in strength and its long-term effectiveness remains questionable. SEM and EBSD were used to document the locus and orientation-dependence of grain boundary failure while TEM was used to determine species present at grain boundaries susceptible to environmentally-enhanced fracture. SSRT testing of S-T samples in various environments revealed different degrees of embrittlement depending on the environment and degree of sensitization. A change in alloy sensitization kinetics occurs at around 100 °C.